Innovation in Education with Impact on Development: Bibliometric Analysis and Mapping in 2024-2025 of Islamic Education - Elihami Elihami; Muwafiq Ibrahim Mas’ud; Alvin S. Sicat; Ismail Ismail; Syawal Sitonda; M Yunus Sudirman (Journal of Innovation in Educational and Cultural Research, 2025)
The revitalization of Islamic education has gained increasing scholarly attention due to global socio-political shifts and rapid technological advancements. This study employs bibliometric analysis and mapping to examine the evolving research landscape from 2024 to 2025. The study identifies key publications, influential authors, and emerging themes using systematic data collection, citation analysis, and visualization techniques. Findings reveal significant research trends, global collaboration patterns, and the field's intellectual structure. The study highlights the growing academic recognition of the need to preserve cultural heritage and enhance religious literacy. This research contributes to a deeper understanding of Islamic education's development by providing a comprehensive overview of scholarly discourse. The insights generated offer valuable implications for researchers, policymakers, and educators, guiding future studies, shaping policy directions, and improving educational practices in this critical area.